EFFECT OF THE TOOL GEOMETRY AND WELDING PARAMETERS ON THE MACROSTRUCTURE, FRACTURE MODE AND WELD STRENGTH OF FRICTION-STIR SPOT-WELDED POLYPROPYLENE SHEETS - (:unkn) unknown (INST ZA KOVINSKE MATERIALE I IN TEHNOLOGIE, 2014)
The effect of the tool geometry and welding parameters on the macrostructure, fracture mode and weld strength of the friction-stir spot welds of polypropylene sheets was studied. Three fracture modes were observed: the nugget pull-out failure, the cross-nugget failure and the mixed nugget failure under a lap-shear tensile test and nugget debonding and a pull out under a cross-tension loading, while the lap-shear tensile load was not affected significantly by the delay time. The lap-shear tensile load and the nugget thickness increased with the increasing tool rotation speed and dwell time. The macrostructure shows that the welding parameters have a determinant effect on the weld strength (x: the nugget thickness, y: the thickness of the upper sheet). Finally, when different welding parameters were used, different fracture modes of the joints were obtained in the friction-stir spot welding of polypropylene sheets. Based on the experimental observation of the macrostructures, the effect of the welding parameters and tool geometry on the lap-shear tensile load and the fracture mode were discussed.
Keywords: polymers (thermoplastics); polypropylene; friction-stir spot welding; polymer welding; welding parameters; STATIC STRENGTH